The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/eje.12651
|View full text |Cite
|
Sign up to set email alerts
|

Cariology consensus for undergraduates at dental schools in the Caribbean region

Abstract: Aim: To obtain a consensus on the domains of cariology for undergraduates in dental schools in the Caribbean.Materials and Methods: Dental school deans from the Dominican Republic (DR) and Puerto Rico (PR) were invited to participate. Afterwards, 24 cariology faculty members from the dental schools in the DR received a 40-h workshop on the current un-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…37 The CCC was implemented in universities in Brazil, Colombia, Chile, Venezuela, Dominican Republic, and Puerto Rico. [38][39][40][41][42] A survey on the inclusion of cariology education in Spanish-speaking dental schools in LACCs showed that non-operative caries management strategies were not implemented on a regular basis. Moreover, the majority of schools reported focusing on all of the main topics of cariology except those related to behavioral sciences, microbiology, saliva and systemic diseases, caries risk factors, root caries, erosion, and early caries management strategies.…”
Section: Trends Of and Risk Factors For Dental Caries In Laccs: Summary Of Articles 1 And 2 Of This Consensusmentioning
confidence: 99%
“…37 The CCC was implemented in universities in Brazil, Colombia, Chile, Venezuela, Dominican Republic, and Puerto Rico. [38][39][40][41][42] A survey on the inclusion of cariology education in Spanish-speaking dental schools in LACCs showed that non-operative caries management strategies were not implemented on a regular basis. Moreover, the majority of schools reported focusing on all of the main topics of cariology except those related to behavioral sciences, microbiology, saliva and systemic diseases, caries risk factors, root caries, erosion, and early caries management strategies.…”
Section: Trends Of and Risk Factors For Dental Caries In Laccs: Summary Of Articles 1 And 2 Of This Consensusmentioning
confidence: 99%
“…In Colombia, after a consensus was achieved in cariology teaching for undergraduate students in 2012 among most dental schools (94%), CRA was designated as a learning objective. 168 This was also the case with the 100% consensus being achieved among 15 dental schools in the Caribbean region, 12 in the Dominican Republic, and 1 each in Puerto Rico, Jamaica, and Trinidad and Tobago. 169 In Brazil, information about caries risk is disseminated via Public health and Integrated seminars, risk factors, and determinants 170 and taught in a theoretical manner in most dental schools (94%).…”
Section: Discussionmentioning
confidence: 92%
“…10 From then on, a movement for the adoption of Cariology Curricula took place in various countries. [11][12][13][14][15][16] The Spanish Society of Epidemiology and Oral Public Health known as SESPO (Sociedad Española de Epidemiología y Salud Pública Oral) in conjunction with Alliance for a Caries Free Future (ACFF) established in 2019 the Spanish Chapter of ACFF. Its objectives include the following: "ACFF and its Chapters will work towards ensuring that ninety per cent of dental schools and dental associations accept the philosophy behind the 'new' approach of 'caries as a continuum' in order to improve dental caries prevention and management."…”
Section: The State Of Oral Health In Europe Provided By the Platform ...mentioning
confidence: 99%
“…Its objectives include the following: "ACFF and its Chapters will work towards ensuring that ninety per cent of dental schools and dental associations accept the philosophy behind the 'new' approach of 'caries as a continuum' in order to improve dental caries prevention and management." 16 The development of a Cariology Curriculum for dental degree students is one of the objectives of the Spanish chapter of the ACFF. 17…”
Section: The State Of Oral Health In Europe Provided By the Platform ...mentioning
confidence: 99%